Assembly of polyethyleneimine in the hexagonal mesophase of nonionic surfactant: effect of pH and temperature - Sharma, Kamendra P.; Choudhury, Chandan Kumar; Srivastava, Sonal; Davis, Hilda C.; Rajamohanan, P. R.; Roy, Sudip; Kumaraswamy, Guruswamy (Journal of Physical Chemistry B, 2011)
We investigate the dispersion of a pH responsive polymer, polyethyleneimine, PEI, in a hexagonal (H(1)) mesophase of a nonionic surfactant, C(12)E(9), and water, at pH ranging from basic (pH = 12.8) to acidic (pH = 1). While the C(12)E(9)/H(2)O phase behavior is independent of pH, we demonstrate that, in the PEI/C(12)E(9)/H(2)O system, changing the pH influences PEI-C(12)E(9) interactions, and thus, influences the isotropic-H(1) phase transition. With decrease in pH, there is increasing protonation of the PEI chain, and consequently, the chain extends. We show, using a combination of SAXs, optical microscopy and visual experiments, that the inclusion of PEI in a 1:1 surfactant water mixture, lowers the hexagonal-isotropic transition temperature, T. At higher pH = 12.8 T(HI) shows a pronounced decrease from SO to 13 degrees C on addition of PEI, and the PEI/C(12)E(9)/H(2)O system forms a transparent gel. At pH = 1, we observe qualitatively different behavior and an opaque gel forms below T(HI)= 25 degrees C. The isotropic-H(1) transition, in turn, influences the phase separation of PEI chains from the C(12)E(9)/H(2)O system. 2D NMR ROESY data provides evidence that there are strong surfactant PEI interactions at high pH that significantly reduce at lower pH. The NMR data is in accord with molecular dynamics simulations that show that surfactants strongly aggregate with unprotonated PEI chains, but not with fully protonated chains; thus, in this system, the pH controls a cascade of microstructural organization: increasing pH decreases chain protonation and increases polymer-surfactant interactions, resulting in suppression of the isotropic-H(1) transition to lower temperatures, thus, influencing the phase separation of PEI from the surfactant/water system.

Molecular dynamics simulation of phosphoric acid doped monomer of polybenzimidazole: a potential component polymer electrolyte membrane of fuel cell - Pahari, Swagata; Choudhury, Chandan Kumar; Pandey, Prithvi Raj; More, Minal; Venkatnathan, Arun; Roy, Sudip (Journal of Physical Chemistry B, 2012)
Phosphoric acid doped polybenzimidazole is promising electrolyte membranes for high temperature (100 degrees C and above) fuel cells. Proton conduction is governed by the amount of phosphoric acid content in the polymer membrane. In this present work, we perform molecular dynamics simulations on phosphoric acid doped 2-phenyl-1H,1'H-5,5'-bibenzo[d]imidazole (monomer unit of polybenzimidazole) to characterize the structural and dynamical properties at varying phosphoric acid content and temperature. From the structural analysis, we have predicted the arrangement of the phosphoric acids, formation of H-bonds in the system, and the contribution of different atoms toward H-bonding. We have also examined the stacking of 2-phenyl-1H,1'H-5,5'-bibenzo[d]imidazole molecules and how their arrangement changes with the increasing amount of PA in the system with the help of cluster analysis. From the molecular dynamics simulation conducted at different temperatures and phosphoric acid doping level, we have predicted the diffusion of phosphoric acid and monomer. As a dynamic quantity, we have also calculated ring flipping of the imidazole ring of the monomer.

Characterization of conformation and interaction of gene delivery vector polyethylenimine with phospholipid bilayer at different protonation state - Choudhury, Chandan Kumar; Kumar, Abhinaw; Roy, Sudip (Biomacromolecules, 2013)
Polyethylenimine (PEI) is a pH sensitive polymer possessing stretched and coiled conformation at low and high pH, respectively. It is an efficient gene delivery agent. Thus, the interaction of PEI with the biomembrane is very crucial to understand the gene delivery mechanism. In this report, we have investigated the structural properties of PEI and bilayer due to the interaction of PEI with lipid molecules. PEI has coil structure at high pH while at low pH it is elongated. The neutral PEI chain predominately settles itself at the bilayer water interface. We do not find any disruption or pore formation on the bilayer due to interaction of neutral PEI chain. PEI at low pH gets elongated due to electrostatic interaction between charges of the protonated sites. This protonated PEI chain interacts with bilayer membrane, which leads to formation of water/ion channel through the membrane. We have analyzed the structure of the channel and water dynamics along the channel.

Morphology and dynamics of carbon nanotube in polycarbonate carbon nanotube composite from dissipative particle dynamics simulation - Chakraborty, Souvik; Choudhury, Chandan Kumar; Roy, Sudip (Macromolecules, 2013)
Morphology and dynamics of carbon nanotube (CNT) in polycarbonate matrix with different mixing ratios are studied in mesoscale by using dissipative particle dynamics (DPD). We have used atomistic simulation to derive necessary interaction parameter for mesoscale DPD simulation for polycarbonate nanotube composite using Flory-Huggins theory. The diffusion and morphology of nanotubes in different concentrations (2%, 5%, 10%) are investigated. Diffusivity of nano tubes in polymer matrices is explored at different temporal regimes of simulation. Diffusion of nanotubes becomes significantly slow when bundling of nanotubes takes place. The bundle formation of nanotubes is observed in all of three mixtures with varying degrees of assembling and alignment Bundle size analysis is performed to study the extent of bundling affinity of CNTs in different filler concentrations. Size of the bundles of nanotubes is more in higher nanotube concentrations. In the 10% mixture percolation network is found to be formed by bundles of nanotubes.

Structural and dynamical properties of polyethylenimine in explicit water at different protonation states: a molecular dynamics study - Choudhury, Chandan Kumar; Roy, Sudip (Soft Matter, 2013)
PEI is a pH sensitive polymer which acts as a proton sponge in acidic conditions. Despite many experimental and theoretical efforts, a fundamental understanding of the structure and dynamics of linear PEI chains on the atomistic level at different protonation states in dilute solutions remains a topic of discussion. This report analyses the structural properties of PEI at different protonation states, which are representative of different pH, using all atomistic molecular dynamic simulations. The structural properties revealed that the polymer at high pH (basic medium) is highly coiled, while at low pH (strong acidic conditions) the chains are elongated. We studied the dynamics and ordering of water molecules that are part of the solvation shells of the PEI chains at different protonation states. We observe that the water molecules are ordered along the polymer backbone for a completely protonated PEI chain (i.e. in the case of acidic pH) and hop to the neighbouring solvation shell. The residence time and the self-diffusion of water molecules in the solvation shells and their activation barriers were also calculated and analysed further. We concluded the study by correlating the solvation shell water dynamics and the structure of the PEI chain at different protonation states.

Compact polar moieties induce lipid-water systems to form discontinuous reverse micellar phase - Kumar, Manoj; Patil, Naganath G.; Choudhury, Chandan Kumar; Roy, Sudip; Ambade, Ashootosh V.; Kumaraswamy, Guruswamy (Soft Matter, 2015)
The role of molecular interactions in governing lipid mesophase organization is of fundamental interest and has technological implications. Herein, we describe an unusual pathway for monoolein/water reorganization from a bicontinuous mesophase to a discontinuous reverse micellar assembly, directed by the inclusion of polar macromolecules. This pathway is very different from those reported earlier, wherein the Fd3m phase formed only upon addition of apolar oils. Experiments and molecular dynamics simulations indicate that hydrophilic ternary additives capable of inducing discontinuous phase formation must (i) interact strongly with the monoolein head group and (ii) have a compact molecular architecture. We present a detailed investigation that contrasts a monoolein-water system containing polyamidoamine (PAMAM) dendrons with one containing their linear analogs. The Fd3m phase forms only on the addition of PAMAM dendrons but not their linear analogs. Thus, the dendritic architecture of PAMAM plays an important role in determining lipid mesophase behavior. Both dendrons and their linear analogs interact strongly with monoolein through their amine groups. However, while linear polymers adsorb and spread on monoolein, dendrons form aggregates that interact with the lipid. Dendrons induce formation of an intermediate reverse hexagonal phase, which subsequently restructures into the Fd3m phase. Finally, we demonstrate that other additives with compact structures that are known to interact with monoolein, such as branched polyethylenimine and polyhedral silsesquioxane cages, also induce the formation of the Fd3m phase.

Colloidal assembly by ice templating - Kumaraswamy, Guruswamy; Biswas, Bipul; Choudhury, Chandan Kumar (Faraday Discussions, 2016)
We investigate ice templating of aqueous dispersions of polymer coated colloids and crosslinkers, at particle concentrations far below that required to form percolated monoliths. Freezing the aqueous dispersions forces the particles into close proximity to form clusters, that are held together as the polymer chains coating the particles are crosslinked. We observe that, with an increase in the particle concentration from about 106 to 108 particles per ml, there is a transition from isolated single particles to increasingly larger clusters. In this concentration range, most of the colloidal clusters formed are linear or sheet like particle aggregates. Remarkably, the cluster size distribution for clusters smaller than about 30 particles, as well as the size distribution of linear clusters, is only weakly dependent on the dispersion concentration in the range that we investigate. We demonstrate that the main features of cluster formation are captured by kinetic simulations that do not consider hydrodynamics or instabilities at the growing ice front due to particle concentration gradients. Thus, clustering of colloidal particles by ice templating dilute dispersions appears to be governed only by particle exclusion by the growing ice crystals that leads to their accumulation at ice crystal boundaries.

Probing the ATP-induced conformational flexibility of the PcrA helicase protein using molecular dynamics simulation - Mhashal, Anil R.; Choudhury, Chandan Kumar; Roy, Sudip (Journal of Molecular Modeling, 2016)
Helicases are enzymes that unwind double-stranded DNA (dsDNA) into its single-stranded components. It is important to understand the binding and unbinding of ATP from the active sites of helicases, as this knowledge can be used to elucidate the functionality of helicases during the unwinding of dsDNA. In this work, we investigated the unbinding of ATP and its effect on the active-site residues of the helicase PcrA using molecular dynamic simulations. To mimic the unbinding process of ATP from the active site of the helicase, we simulated the application of an external force that pulls ATP from the active site and computed the free-energy change during this process. We estimated an energy cost of similar to 85 kJ/mol for the transformation of the helicase from the ATP-bound state (1QHH) to the ATP-free state (1PJR). Unbinding led to conformational changes in the residues of the protein at the active site. Some of the residues at the ATP-binding site were significantly reoriented when the ATP was pulled. We observed a clear competition between reorientation of the residues and energy stabilization by hydrogen bonds between the ATP and active-site residues. We also checked the flexibility of the PcrA protein using a principal component analysis of domain motion. We found that the ATP-free state of the helicase is more flexible than the ATP-bound state.
Keywords: ATP; DNA helicase; PcrA; Residue reorientation; Translocation; Umbrella sampling; Unwinding

Scalability of coarse-grained potentials generated from iterative boltzmann inversion forpolymers: case study on polycarbonates - Choudhury, Chandan Kumar; Carbone, Paola; Roy, Sudip (Macromolecular Theory and Simulations, 2016)
Using systematic coarse-grained (CG) techniques such as iterative Boltzmann inversion (IBI) is an efficient means to simulate high molecular weight polymer melts within reasonable computational time. One drawback of such an approach is however the need to carry out extensive atomistic simulations in order to extrapolate the necessary distributions to derive the inter and intrabead force field parameters. Here it is shown that it is possible to use atomistic simulations of relative short oligomers to develop the CG model for high molecular weight polymers. In particular for the specific case of polycarbonates, it is found that the structural properties (end-to-end distance, radius of gyration and their distributions) are similar irrespective of whether the CG potentials are derived from 5-mer or 10-mer melt systems. Dynamical properties of the CG systems are smoother and faster than the atomistic ones. Scaling factor, derived by overlapping the CG mean square displacement curves (obtained from different CG IBI potentials) over the atomistic ones, also scales the autocorrelation functions. A prediction of the dynamical scaling factor in the case of the unavailability of atomistic simulations is also discussed. The dynamical properties of the CG melts are modeled reasonably well by all the CG potentials derived from atomistic simulations of short oligomers.

Self-exfoliated guanidinium-based ionic covalent organic nanosheets (iCONs) - Mitra, Shouvik; Kandambeth, Sharath; Biswal, Bishnu P.; Khayum, Abdul M.; Choudhury, Chandan Kumar; Mehta, Mihir R.; Kaur, Gagandeep; Banerjee, Subhrashis; Prabhune, Asmita; Verma, Sandeep; Roy, Sudip; Kharul, Ulhas K.; et al. (Journal of the American Chemical Society, 2017)
Covalent organic nanosheets (CONs) have emerged as functional two-dimensional materials for versatile applications. Although pi-pi stacking between layers, hydrolytic instability, possible restacking prevents their exfoliation on to few thin layered CONs from crystalline porous polymers. We anticipated rational designing of a structure by intrinsic ionic linker could be the solution to produce self-exfoliated CONs without external stimuli. In an attempt to address this issue, we have synthesized three self-exfoliated guanidinium halide based ionic covalent organic nanosheets (iCONs) with antimicrobial property. Self-exfoliation phenomenon has been supported by molecular dynamics (MD) simulation as well. Intrinsic ionic guanidinium unit plays the pivotal role for both self-exfoliation and antibacterial property against both Gram-positive and Gram-negative bacteria. Using such iCONs, we have devised a Mixed matrix membrane which could be useful for antimicrobial coatings with plausible medical benefits.